(untitled) (Damascus University Journal for legal sciences, 2024)
The adoption of a stable real estate registry is one of the most important issues that lead to the strengthening of real estate ownership and the provision of real estate credit. This is what the Syrian legislator worked on when he issued the land Registry Law, and its main goal was to make this system a comprehensive system integrated with its provisions. It secures protection for the owners of real estate restrictions based on its principles, foremost of which is the corroborative power of its restrictions .The protection of real estate is the legislator is the goal of the legislator and can only be achieved by protecting and preserving the principles and restrictions of the real estate registry. Hence, it may be asked whether protection is still available for the right holder based on the record of the real estate registry restrictions that became apparent to him in light of the ruling issued by the Syrian judiciary, especially the decision issued by the Court of Cassation No. /6/ foundation/38/, 2022/3/9.